Agri-food competitiveness in the Andean Community: a study of revealed comparative advantage indices - Rubén Francisco Llerena Tapia; Gianella Alexa Beraun Alegre; Britaly Briggete Carrasco Garcia; Carlos Barja Otero; Miguel Alexander Flores Lamas; Julio Ricardo Moscoso Cuaresma (Cogent Social Sciences)
Despite growth and trade agreements in the Andean Community, the competitiveness of agri-food exports from member countries has not been fully assessed. This study quantifies the competitiveness of these exports during the period 2013-2023 by applying the Revealed Comparative Advantage (RCA) index and a subsequent statistical correlation test to validate the robustness of the data. The results highlight Ecuador as the only country with a significant degree of competitiveness in its agri-food exports. Throughout the period analysed, the countries of the Andean Community show differences in the competitiveness of their agri-food exports, which are mainly reflected in their RCA indices. Ecuador stands out for its high RCA, indicating strong competitiveness, while other countries such as Colombia, Bolivia, and Peru have indices below 1, indicating challenges in innovation and diversification that affect their position in the global agri-food market.